(untitled) (Conversatoria Linguistica, 2019)
The features of Eastern-slavonic antrophonymy of Sławatycze in the early XX century have been described in the article. The antrophonymy of Sławatycze is a reflection of essential lingual interference appropriate to frontier areas. In the inner-lingual sphere, it refers to the issue related to Eastern-slavonic phonology (full-voicing, soft pronouncing hard consonants) and also morphology. The antrophonymys derived from names and ended with genetically Ukrainian suphixal formants are characteristic for this region. Most names were created from orthodox church names. Apart from majority of Ukrainian and Belarussian elements, there are also Russian and Lithuanian ones.